The Use of Verbs And Adjective In JEFL Journal (2021-2023) By Using Corpus Linguistics - Marshanda, Agnes; Riris Mutiara Paulina Simamora (e-LinguaTera, 2025)
Journal is a record the of descriptions or thoughts, written each day or frequently over a longperiod a diary. Education is any condition, matter, incident, event, or process of changing theattitude and behavior of a person or group of people in an effort to mature them through learningand training system. JEFL Journal is the journal that made in Indonesia and provide the educationabout learn and teaching English for the learners. Therefore, this research titled “Analysis ofVerbs and Adjectives in JEFL Journal (2021 – 2023) by Using Corpus Linguistics” purpose to findout the most of verbs and adjective that appear in JEFL Journal in 2021 – 2023 and to know therole of verbs and adjective by categorized. This research using quantitative method to gains thedata by the table. The source data is ten title journal in JEFL Journal each year. To collection datause application AntConc to know most frequently each year and TagAnt to gain the part ofspeech. The result shows the most frequently 2021-2023 is verbs than adjective and the role ofverbs is learn verbs, then the role of adjective is descriptive adjective. The result from thisresearch that most frequently is learn verbs used to do are particularly useful in describingactions. Also, for future research, can use a corpus application to research how many words areused in journals, books or films and can use health or sports objects to research